2015
DOI: 10.1016/j.enbuild.2015.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of frequency-domain finite-difference model of active pipe-embedded building envelope in time domain by using Fourier series analysis

Abstract: a b s t r a c tActive pipe-embedded building envelope is a new kind of external building wall or roof which usually has pipes embedded in it to let water circulate in these pipes for heat transfer. This structure may effectively intercept the heat/coolth from the ambient environment to indoor space and provide extra space conditioning for the indoor space. Frequency-domain finite-difference (FDFD) model can predict the frequency thermal response of active pipe-embedded building envelope directly and provide so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several studies developed theoretical models validated with experimental. These models were used to find the adequate values for pipes separation and pipes depth within the walls [31], [33], [35], [37] water inlet temperature for cooling or heating [30], [37], water velocity and volumetric flow rate [30], [31], [33]. Modeling studies are relevant for the design of TABS because they allow researchers to find suitable values for the parameters mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies developed theoretical models validated with experimental. These models were used to find the adequate values for pipes separation and pipes depth within the walls [31], [33], [35], [37] water inlet temperature for cooling or heating [30], [37], water velocity and volumetric flow rate [30], [31], [33]. Modeling studies are relevant for the design of TABS because they allow researchers to find suitable values for the parameters mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the difference between the analytically calculated average temperature and the experimental measurements is 13.7 and 8.6% by contact and non-contact methods. A research about the thermal behavior of a building wall construction with embedded tubes was developed by Xie et al, [30]. Meanwhile, the average difference of about 0.5°C on the outlet temperature of the fluid was found throughout the day.…”
Section: Tabs Embedded In Building Wallsmentioning
confidence: 99%
“…Many researchers from all over the world have been involved in the analysis of building structures with integrated energy-active elements. We provide references to some of the main scientific studies in this area of research [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Current Situationmentioning
confidence: 99%
“…Xie, Xu, Li and Zhu in [14] describe a frequency-domain active building envelope model (FDFD) with TBs, which can directly predict the frequency thermal response of the active building envelope with integrated pipes and provide some important guidelines for system control and system sizing. This paper presents an experimental validation of this model in the time domain using Fourier series analysis.…”
Section: Description Of the Known State Of The Art And Contribution T...mentioning
confidence: 99%